Mixed Multiracial College Students Tell Their Life Stories - Garrod, Andrew; Gómez, Christina; Kilkenny, Robert (Cornell University Press, 2013)
Mixed presents engaging and incisive first-person experiences of what it is like to be multiracial in what is supposedly a postracial world. Bringing together twelve essays by college students who identify themselves as multiracial, this book considers what this identity means in a reality that occasionally resembles the post-racial dream of some and at other times recalls a familiar world of racial and ethnic prejudice.Exploring a wide range of concerns and anxieties, aspirations and ambitions, these young writers, who all attended Dartmouth College, come from a variety of racial, ethnic, and socioeconomic backgrounds. Unlike individuals who define themselves as having one racial identity, these students have lived the complexity of their identity from a very young age. In Mixed, a book that will benefit educators, students, and their families, they eloquently and often passionately reveal how they experience their multiracial identity, how their parents' race or ethnicity shaped their childhoods, and how perceptions of their race have affected their relationships